Pioglitazone improves whole‐body aerobic capacity and skeletal muscle energy metabolism in patients with metabolic syndrome - Yokota, Takashi (J Diabetes Investig, 2017)
AIMS/INTRODUCTION: Low aerobic capacity is a strong and independent predictor of all‐cause mortality in patients with metabolic syndrome (MetS). Here, we investigated the effects of pioglitazone treatment on whole‐body aerobic capacity and skeletal muscle energy metabolism in MetS patients. MATERIALS AND METHODS: A total of 14 male patients with MetS received oral pioglitazone 15 mg/day for 4 months. To assess whole‐body aerobic capacity, exercise testing with a bicycle ergometer was carried out before and after pioglitazone treatment. To assess skeletal muscle energy metabolism, intramyocellular lipid in the resting leg and high‐energy phosphates in the calf muscle during plantar‐flexion exercise were measured using (1)proton‐ and (31)phosphorus magnetic resonance spectroscopy, respectively. RESULTS: Pioglitazone significantly increased peak oxygen uptake (25.1 ± 4.9 mL/kg/min pretreatment vs 27.2 ± 3.9 mL/kg/min post‐ treatment, P < 0.05) and anaerobic threshold (12.7 ± 1.9 mL/kg/min pretreatment vs 13.6 ± 1.6 mL/kg/min post‐treatment, P < 0.05), although daily physical activity was comparable before and after the treatment. Intramyocellular lipid content was significantly reduced after pioglitazone treatment by 26%, indicating improved skeletal muscle fatty acid metabolism. Pioglitazone also significantly decreased the muscle phosphocreatine loss during exercise by 13%, indicating improved skeletal muscle high‐energy phosphate metabolism. Notably, the increase in anaerobic threshold; that is, submaximal aerobic capacity, closely correlated with the decrease in intramyocellular lipid content after pioglitazone treatment. CONCLUSIONS: Pioglitazone significantly improved the MetS patients’ whole‐body aerobic capacity and skeletal muscle energy metabolism. The beneficial effect of pioglitazone on whole‐body aerobic capacity might be at least in part through improved fatty acid metabolism in the skeletal muscle.